The United States' Strategies to Undermine Japan in Palembang During World War II via Operation Matterhorn, 1944 - Ardi Tri Yuwono; Helen Jayla Lansford (Perkumpulan Program Studi Sejarah Se-Indonesia, 2026)
During World War II in the Pacific region, Palembang functioned as the main center of oil production in the Southeast Asian region. This area and its oil refinery facilities were controlled by Japanese forces on February 15, 1942 in a battle known as the Battle of Palembang. In response, the United States planned an attack on the Plaju Oil Refinery in Palembang with the aim of weakening Japanese power through an operation called Matterhorn. This research aims to dig deeper into the Operation Matterhorn which took place in the city of Palembang. The method used in this study is a historical method with a qualitative approach. In the implementation of Operation Matterhorn (August 10-11, 1944), the United States bombed the Plaju Oil Refinery in Palembang using Boeing B-29 Superfortress aircraft. In addition, the aircraft was also used to spread mines in the Musi River, with the aim of disrupting the shipping lanes of Japanese ships carrying oil. During the Matterhorn operation in Palembang, areas such as Padang City, especially the Indarung Cement Factory, and Jambi City also experienced the impact of air attacks, because these areas were used as alternative missions if the bombing in Palembang was unsuccessful.